THE DEVELOPMENT OF ATTITUDES TOWARDS AUTHORITY IN CHILDREN - Kenneth, Sharrat (My University, 1969)
This study is concerned with the way in which school CHILDREN ACQUIRE FEELINGS FOR THE PRIME MINISTER OF CANADA AND THE policeman. There are four main objectives to this research project. The first aspect is concerned with the child’s evaluation of each authority. This is essentially a mapping operation in which the CHILD EVALUATES THE PRIME MINISTER AND THE POLICEMAN AGAINST A BACKDROP OF ’MOST OTHER MEN*. THE OBJECTIVE OF THIS STUDY IS AN EXAMINATION OF THE INFLUENCE OF AGE, SEX, POLITICAL PARTY AFFILIATION AND SOCIAL CLASS UPON THE APPRAISAL OF POLITICAL AUTHORITY. THE THIRD OBJECTIVE IS CONCERNED TO PROVIDE A COMPARISON OF THIS Canadian data with recent published American data. The saliency OF the national leaders in the two countries can be determined FROM THE STUDENT’S EVALUATIONS. THE ITEMS HAVE BEEN SELECTED TO PROVIDE COMPARABILITY BETWEEN CANADIAN AND AMERICAN DATA. THE FINAL OBJECTIVE INVOLVES AN EVALUATION OF EFFICACY OF THE THEORIES WHICH PURPORT TO ACCOUNT FOR THE CHILD’S PERCEPTION OF POLITICAL AUTHORITY. Chapter one outlines the objectives of this study and provides A REV 1 EV/ OF THE RECENT LITERATURE. Chapter two is concerned with the child’s knowledge of the Prime Minister’s name and political party affiliation. Age, sex, POLITICAL PARTY PREFERENCE AND SOCIAL CLASS ARE EXAMINED TO DETERMINE THE INFLUENCE OF THESE GROUPINGS UPON THE CHILD’S LEVEL OFPOLITICAL KNOWLEDGE. Chapters three through seven are concerned with the child’s FEELINGS FOR AUTHORITY. THE CHILD WILL BE PROVIDED WITH FIVE DIMENSIONS ON WHICH TO EXPRESS HIS FEELINGS FOR AUTHORITY. THESE DIMENSIONS HAVE BEEN ARRANGED FROM THE MOST PERSONAL FEATURES OF LIKING AND PERCEPTIONS OF BENEVOLENCE TO THE MORE INSTITUTIONAL ASPECTS OF POLITICAL AUTHORITY HAVING TO DO WITH POWER AND LEADERSHIP. Chapter three is concerned with the child’s liking for AUTHORITY, CHAPTER FOUR WITH THE CHILD’S PERCEPTION OF BENEVOLENCE, Chapter five with authority dependability, Chapter six with power PERCEPTIONS AND CHAPTER SEVEN WITH THE EVALUATION OF THE LEADERSHIP ABILITIES OF THE PRIME MINISTER AND POLICEMAN. Chapter eight concludes this study by answering questions RAISED IN RELATION TO THE FOUR OBJECTIVES OF THE STUDY SET OUT IN THE FIRST CHAPTER. The author is grateful for the programming assistance of Mrs K. Strano and the cooperation extended by other members of the McMaster data processing and computing centre. The author also acknowledges the kind assistance provided in the early stages of THIS STUDY BY MR. W. K. M. ARMSTRONG, SUPER 1NTENDENT.OF OAKVILLE Public Schools, enabling this study to be carried out at short notice. Thanks, also, to the principals of the Oakville public schools for their wholehearted cooperation in arranging time for the administration of the questionnaire.